2021
DOI: 10.3390/children8030232
|View full text |Cite
|
Sign up to set email alerts
|

Feeling Unsafe at School and Associated Mental Health Difficulties among Children and Adolescents: A Systematic Review

Abstract: This study systematically reviewed the literature on perceived school safety. We investigated the prevalence, factors and associated mental health difficulties, as well as cross-cultural findings. Five databases were searched up to 9 February 2021 for peer-reviewed papers published in English. We included quantitative studies that explored the perception of school safety among children and adolescents. The reference lists of the selected papers were also searched. We conducted a narrative synthesis of the incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 95 publications
1
22
0
1
Order By: Relevance
“…Whereas school nurse scope of practice includes mental health services for students, previous work has noted a lack of appropriate training, and large caseloads of students 19 . A scoping review suggests that identification of mental health needs and school‐based interventions are currently central activities of school nurses, 19 and in one program, school nurse use of validated screening tools for depression and anxiety resulted in improved identification, care coordination, and referral for students, 20 which may be particularly compelling considering recent findings in a systematic review that found perceived safety is associated with mental health challenges, including suicidal behavior 21 …”
Section: Conflict Of Interestmentioning
confidence: 99%
“…Whereas school nurse scope of practice includes mental health services for students, previous work has noted a lack of appropriate training, and large caseloads of students 19 . A scoping review suggests that identification of mental health needs and school‐based interventions are currently central activities of school nurses, 19 and in one program, school nurse use of validated screening tools for depression and anxiety resulted in improved identification, care coordination, and referral for students, 20 which may be particularly compelling considering recent findings in a systematic review that found perceived safety is associated with mental health challenges, including suicidal behavior 21 …”
Section: Conflict Of Interestmentioning
confidence: 99%
“…Substance use is associated with suicidality in adolescents ( 10 ), including illicit drugs ( 13 , 14 ), marijuana ( 14 , 15 ), alcohol ( 13 , 15 ), and tobacco ( 13 , 15 ). Psychosocial stressors and adverse childhood experiences also are associated with suicidality, including cyberbullying ( 16 18 ); not feeling safe at school ( 19 ); and sexual abuse, physical abuse, emotional abuse, and neglect ( 20 23 ).…”
Section: Introductionmentioning
confidence: 99%
“…Perceived school safety has mainly been studied in western countries. A recent systematic review of 43 studies showed the mean occurrence of unsafe school environments was ~19% and ranged from 6.1 to 69.1% ( 2 ). Feeling safe at school has been reported to be associated with various predictors, including bullying and youth violence ( 3 , 4 ), lower academic achievements ( 5 ) and better relationships with teachers ( 6 ).…”
Section: Introductionmentioning
confidence: 99%
“…According to the systematic review, most of the studies on perceived school safety were published between 2016 and 2020, indicating an increasing research interest in this topic ( 2 ). However, very few cross-national studies have been conducted and all of these only compared perceived school safety between two countries ( 11 13 ).…”
Section: Introductionmentioning
confidence: 99%